Composition, Conservation Status, and Market Value of Fish Landed at the Labuhan Haji Fishing Port, Aceh, Indonesia - Epa Paujiah; Ilham Zulfahmi; Junaidi M. Affan; Musda Fina; Badratun Nafis (Jurnal Penelitian Pendidikan IPA, 2024)
Labuhan Haji Fishing Port (PPP) is the only type C port in the South Aceh. Several types of fish categorised as near threatened and vulnerable, including sharks and rays, are still caught and traded at Labuhan Haji PPP.. This research aims to determine the species composition, species conservation status, and economic value of fish landed at Labuhan Haji PPP South Aceh. This research was conducted in July-August 2022 at the Labuhan Haji Coastal Fishing Port (PPP), Pasar Lama Village, Labuhan Haji District, South Aceh Regency. Identification of fish types is carried out by matching the morphological characteristics of the fish with the morphological characters referring to https://www.fishbase.se/se/search.php. The conservation status of fish species refers to the red lists from IUCN (International Union for the Conservation of Nature), CITES (Convention on International Trade in Endangered of Wild Flora and Fauna), and KEPMEN-KP/1/2021 regarding protected fish species. The economic value of fish was obtained through brief interviews with fish traders at the research site. Besides, the data collected includes the selling price range for fish at Labuhan Haji PPP. The research results showed that Perciformes was the most frequently found order at 37% (26 species, 10 families), and Carangidae was the most frequently found family at 19% (13 species). Based on the IUCN red list, 64% Least concern, 9% Not evaluated, 7% Data deficient, 7% Vulnerable, 6% Near Threatened, 4% Endangered, and 3% Critically endangered. Based on CITES, 7% is recorded as Appendix II, and 93% is not evaluated. Based on Ministerial Decree No.1 KEPMEN-KP/2021 concerning Protected Fish Types, no species are listed as protected fish species in Indonesia. The fish with the highest economic value are from the Serranidae family, with an average price of IDR. 63,333 /Kg and the type of fish with the lowest selling price is from the Mobulidae family, which has an average price of Rp. 8,500/Kg. The types of fish landed at Labuhan Haji PPP are caught using purse seines, gill nets, fishing rods, and floating charts (fish aggregating devices).